2021
DOI: 10.1177/2333794x211019695
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Necrotizing Enterocolitis and Associated Factors Among Enteral Fed Preterm and Low Birth Weight Neonates Admitted in Selected Public Hospitals in Addis Ababa, Ethiopia: A Cross-sectional Study

Abstract: Necrotizing enterocolitis (NEC) remains to be the most critical and frequent gastrointestinal disorder understood in neonatal intensive care units (NICU). The presented study was intended to assess the prevalence of NEC and associated factors among enteral Fed preterm and low birth weight neonates. Institution based retrospective cross-sectional study was conducted on 350 enteral Fed preterm and low birth weight neonates who were admitted at selected public hospitals of Addis Ababa from March 25/2020 to May 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 43 publications
1
24
1
2
Order By: Relevance
“…But, the finding was lower than studies conducted in Addis Ababa, Ethiopia (25.4%). 5 This difference might be due to the differences in population segment, as the study in Addis Ababa includes low birth weight infants as an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But, the finding was lower than studies conducted in Addis Ababa, Ethiopia (25.4%). 5 This difference might be due to the differences in population segment, as the study in Addis Ababa includes low birth weight infants as an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined using a single population proportion using the proportion of NEC 25.4%. 5 Assuming the Z α/2=critical value for normal distribution at 95% confidence level, 5% margin of error (W). After adding a 5% non-response rate, the final sample size was 288.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with those of various authors who have studied the risk factors for NEC and found that low birth weight is the most frequently mentioned significant risk factor for NEC in newborns in the modern literature, which is consistent with studies describing the highest incidence of NEC among infants with the lowest body weight at birth. These authors also show that severe RDS was a significant risk factor for the development of NEC [2]. Mechanical ventilation, newborn weight, and maternal age have also been associated with an increased risk of NEC [2,7,8].…”
Section: Introductionmentioning
confidence: 74%
“…The most complex and least studied problem in neonatology is necrotizing enterocolitis (NEC). The vast majority of children with NEC are premature babies with a body weight less than 1500 g. According to various authors, NEC occurs at a frequency of 2-10 per 1000 premature babies with very low and extremely low birth weight [1,2]. Surgical stages of NEC occur on average in 50% of sick children, mortality in this case reaches 20%, and with extensive intestinal necrosis it can reach 80-100%.…”
Section: Introductionmentioning
confidence: 99%